Seismic Response Analysis of Structure with Cooperation of Laminated Rubber Bearing and Wind-Resistant Support - 吴应雄 王兆樑 林树枝 林婷婷 (东华大学学报（英文版）, 2014)
The purpose is to study the seismic reduction effect of an isolated structure,with wind-resistant bearings（ WRBs） setting on its isolation layer to withstand great wind load,and the working mechanism of the WRB. In this paper,two isolation models with /without WRBs,taking an actual engineering as the background,are established in the finite element software ETABS. The one with WRBs has horizontal damping coefficient less than 0. 40 while the other between 0. 40 and 0. 53. WRBs are simulated by Plastic 1element and the collaborative work between them and isolation layer is described by a mechanical model. Time history analysis is conducted on the models to compare their responses under earthquake excitations. Results show that the one with WRBs,but less lead-rubber bearings（ LRBs）,has better damping effect than the other,although they both can meet wind requirements. It is also shown that under normal conditions and small earthquakes,WRBs function well and the isolation layer will not yield; under moderate earthquakes,WRBs will yield and be destroyed to stop functioning but without affecting the damping effect of the upper structure.Additionally, the total yield shear force provided by LRBs is proposed to be close to the standard value of wind load.